2011
DOI: 10.1007/jhep06(2011)077
|View full text |Cite
|
Sign up to set email alerts
|

Search for new physics with same-sign isolated dilepton events with jets and missing transverse energy at the LHC

Abstract: Abstract:The results of searches for new physics in events with two same-sign isolated leptons, hadronic jets, and missing transverse energy in the final state are presented. The searches use an integrated luminosity of 35 pb −1 of pp collision data at a centre-of-mass energy of 7 TeV collected by the CMS experiment at the LHC. The observed numbers of events agree with the standard model predictions, and no evidence for new physics is found. To facilitate the interpretation of our data in a broader range of ne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
42
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 27 publications
0
42
0
Order By: Relevance
“…The Compact Muon Solenoid (CMS) Collaboration recently published a search for new physics in events with same-sign isolated dileptons, jets, and E / T [1]. The results of that search are recast in this short Letter to set constraints on the production of same-sign top-quark pairs at the Large Hadron Collider (LHC).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The Compact Muon Solenoid (CMS) Collaboration recently published a search for new physics in events with same-sign isolated dileptons, jets, and E / T [1]. The results of that search are recast in this short Letter to set constraints on the production of same-sign top-quark pairs at the Large Hadron Collider (LHC).…”
mentioning
confidence: 99%
“…Thus, the final state of interest contains two high transverse momentum (p T ) isolated positive leptons (e + or µ + ), two or more jets, and missing transverse energy (E / T ) from two neutrinos. The result presented here is based on an already published search for new physics in events with same-sign isolated dileptons, jets, and E / T [1]. In that search we presented event yields and background expectations for a number of event selections sensitive to different possible new physics contributions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, negative LHC SUSY searches have also suggested that the SUSY spectrum might be far heavier than what had previously been considered [89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107]. Moreover, the sensitivity of the experiments dedicated to the observation of low-energy cLFV transitions has also significantly improved [108], especially in what concerns µ → eγ decays [109] and µ − e conversion in nuclei [110,111].…”
Section: Jhep08(2012)138mentioning
confidence: 99%
“…The low-energy sparticle masses and mixings have been numerically evaluated with the SPheno public code [121]. LHC bounds on the SUSY spectrum [89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107] have been applied; in all cases, the lightest Higgs mass is around 117 GeV, still marginally compatible with the new LHC data [122,123]. Notice that the non-minimal SUSY scenarios can still be considered to accommodate such data, with a minimal impact concerning the present lepton flavour dedicated analysis.…”
Section: Jhep08(2012)138mentioning
confidence: 99%